ISO/TS 16949 system in quality aspect - Joanna Rosak-Szyrocka; Stanisław Borkowski (Production Engineering Archives, 2014)
In the automotive industry the use of modern technology and provision of the highest quality product and related services is the most important element of rivalry between global corporations and motorcycles. In a competitive struggle for the recognition of its brand in the automotive market global organizations continuously raise the requirements for quality management systems, so that the finished product meets all the standards in terms of safety, quality and satisfying the ever-growing needs of customers - present and future drivers and passengers of cars. ISO/TS 16949 quality management system is presented in the paper. A framework for customer specific requirement as well as preventing problems is shown.